IDENTIFYING IMPULSE BUYING BEHAVIOR AMONG STUDENTS: THE ROLE OF FINANCIAL ATTITUDE AND LIFESTYLE - Safina, Putri Della; Widyastuti, Umi; Krissanya, Nofriska (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study tries to see how financial attitudes can affect impulse purchases, lifestyle can affect impulse purchases, financial attitudes can affect lifestyle, and financial attitudes affect impulse purchases through lifestyle among students in the Greater Jakarta area. This study uses a survey method. Data collection using sampling techniques using non-probability techniques. Sampling of 200 respondents from the Greater Jakarta area who have made impulse purchases. Including respondents who make purchases without prior planning and buy goods only on a whim. This study uses SEM-PLS (Structural Equation Modeling Partial Least Square) with SmartPLS 4.0 software. This study proves that: (1) Financial Attitudes affect Impulse Buying, (2) Financial Attitudes affect lifestyle, (3) Lifestyle affects Impulse Buying, and (4) Financial Attitudes affect Impulse Buying through lifestyle.